The Effect of Individual Personality, Capabilities, Commitments and Work Facilities on Performance of Employees of the Regional Disaster Management Agency of Labuhanbatu Regency - Muhammad Soleh; Elvina Elvina; Abd. Halim; Zuriani Ritonga (Budapest International Research and Critics University, 2022)
This research was conducted at the Regional Disaster Management Agency of Labuhanbatu Regency, with the aim of analyzing the influence of individual personality, ability, commitment and work facilities on employee performance, either simultaneously or partially. The results of the study indicate that partially and simultaneously, all independent variables have a positive and significant influence on employee performance, this can be proven by the t test and F test. The results of the t test can be described as follows, the individual personality variable (X1) has a tcount value (3.59) > ttable (1.66) which means Ha is accepted and Ho is rejected. While the significant value is smaller than the probability value of 0.05 or a significant value of 0.001 <0.05. Thus it can be concluded that the individual personality variable (X1) has a positive and significant effect on employee performance. Ability (X2) has a value of tcount (4.08) > ttable (1.66) which means Ha is accepted and Ho is rejected. While the significant value is smaller than the probability of 0.05 or 0.000 <0.05. Thus it can be concluded that the ability (X2) has a positive and significant effect on employee performance. Commitment (X3) has a value of tcount (6.56) > ttable (1.66) which means Ha is accepted and Ho is rejected, while the significant value is less than the probability of 0.05 or 0.000 <0.05. Thus it can be concluded that commitment (X3) has a positive and significant effect on employee performance. Work facilities (X4) have a value of tcount (9.30) > ttable (1.66) which means Ha is accepted and Ho is rejected, while the significant value is less than the probability of 0.05 or 0.000 <0.05. Thus it can be concluded that work facilities (X4) have a positive and significant effect on employee performance. The value of Fcount is 148.39 > Ftable 2.47 with a significance value of 0.000 <0.05. From these results, it can be concluded that individual personality, ability, commitment and work facilities simultaneously have a positive and significant influence on employee performance.